The relationship between empowerment and employee performance at Politeknik Tuanku Syed Sirajuddin (PTSS), Ulu Pauh, Perlis / Suraika Zai - Zai, Suraika (2017)
The purpose of this study is to identify the relationship between empowerment and employee performance among employee in Malaysia. The research has been done at Politeknik Tuanku Syed Sirajuddin (PTSS), Ulu Pauh, Perlis. The independent variables in this study are serving others, monitoring others, mentoring others and coaching others. Research design of this research is non-experimental research which is correlational research. The sampling techniques that been used is stratified sampling. The unit of analysis for this research is individual respondent. There are total 33 questions in questionnaire and the questionnaire is analyze by used Statistical Package for Social Science (SPSS) version 20. The objectives of this study are to determine the relationship between empowerment and employee performance. The result of this study has been shows that there are significance, positive and moderate relationship between empowerment and employee performance at Politeknik Tuanku Syed Sirajuddin (PTSS) (r=.554, n=80, p<0.01). The factors that have been practiced in Politeknik Tuanku Syed Sirajuddin (PTSS) are serving employee, monitoring employee, mentoring employee and coaching employee, however the highest and the most affect are serving employee and the total mean for servig employee are 3.9850, monitoring employee are 3.8719, mentoring employee are 3.8250, and coaching employee are 3.8265. The recommendations that recommended organization should establish a mentoring program in an organization so that the junior or new employee can get limitless education and experience from the senior or experienced employee, Effective mentoring was needed in many ways so that the mentoring will be more and much better also more accurate then everyone can get as much as possible benefits from mentoring, and organization should know and aware with the current situation about what is going on around so that the organizations not left behind due to careless. Organization must understand what activities are necessary to provide effective mentoring for beginning principals.